Effects of mannuronic acid (M2000) on gene expression profile of signal transducer and activator of transcription proteins (STATs) in rheumatoid arthritis patients - N.A.G. Gaafar; M. Aslani; Z. Aghazadeh; S.S. Mortazavi-Jahromi; A. Razavi; A. Mirshafiey (PAGEPress Publications, 2020)
Rheumatoid arthritis (RA), a form of inflammatory arthritis, is a chronic joint disease characterized by pain and inflammation that affects 0.5% to 1% of the population worldwide. The safety, efficacy, tolerability, and potency of β-D-mannuronic acid (M2000) as a novel NSAID with immunosuppressive property has been reported by several in vitro studies, experimental models and clinical trials phase I/II and III in ankylosing spondylitis and rheumatoid arthritis (RA) patients This research is designed to study the therapeutic efficacy of oral administration of mannuronic acid in RA patients who had inadequate response to conventional drugs and to assess the effect of this drug on gene expression of the signal transducer and activator of transcription (STATs) protein (STAT1, STAT3, STAT4, and STAT6). The study has included 15 RA patients who had an insufficient response to the conventional therapy. The oral dose of mannuronic acid was 1000mg divided into two 500 mg doses per day for 3 months as an addition to conventional therapy. There were 15 healthy volunteer in the control group. Blood samples were collected from both groups, once from healthy controls and twice from RA patients before and after treatment by M2000. The peripheral blood mononuclear cells (PBMCs) were isolated to assess the gene expression level of STAT1, STAT3, STAT4, and STAT6 using the real-time PCR method. Results obtained in this study demonstrated a significant difference in the gene expression level of STAT1 between healthy controls and patients before treatment as well as a significant reduction in RA patients after treatment compared with the level before treatment. In addition, the gene expression level of STAT3 and STAT4 showed a significant reduction in RA patients after treatment compared to patients before treatment, while there was no significant difference between RA patients before treatment and the healthy control group for both molecules. On the other hand, there was no change in the gene expression level of STAT6 among all groups. The outcomes of this study confirmed that β-D-mannuronic acid (M2000) has the ability to control the levels of STAT1, STAT3 and STAT4 in RA patients, and might be beneficial in the management and therapy of RA.